EFEKTIVITAS DAN PERFOMANCE WEBSITE DINAS PEMERINTAHAN DI LINGKUNGAN PEMERINTAH KOTA PALEMBANG SEBAGAI MEDIA PELAYANAN PUBLIK - Agustina, Merry (Universitas Bina Darma, 2014)
Palembang City Government using the website as a communication media in providing services to people with addresses pubilk www.palembang.go.id, and followed by all agencies with the vision, mission, tasks and responsibilities of each. This study aims to assess the perfomance website government agencies within the city of Palembang and effective use of websites as a medium of public service in the public service within the city of Palembang by eight service elements are simplicity, clarity, security, transparency, efficient, economical, fairness and timeliness by the respondent amounted 305. The results showed an overall data processing perfomance website are in good enough condition, evidenced by the percentage of the four existing criteria. As for the effectiveness of the website as a public service media has not been so effective because there are three elements that are still not good that 43% efficient, economical 46.2% and 32.1% punctuality service.